The hit-and-run of cell wall synthesis: LpoB transiently binds and activates PBP1b through a conserved allosteric switch - Irina Shlosman; Andrea Vettiger; Thomas G. Bernhardt; Andrew C. Kruse; Joseph J. Loparo (Nature Communications)
Abstract The peptidoglycan (PG) cell wall is the primary protective layer of bacteria, making the process of PG synthesis a key antibiotic target. Class A penicillin-binding proteins (aPBPs) are a family of conserved and ubiquitous PG synthases that fortify and repair the PG matrix. In gram-negative bacteria, these enzymes are regulated by outer-membrane tethered lipoproteins. However, the molecular mechanism by which lipoproteins coordinate the spatial recruitment and enzymatic activation of aPBPs remains unclear. Here we use single-molecule FRET and single-particle tracking in E. coli to show that a prototypical lipoprotein activator LpoB triggers site-specific PG synthesis by PBP1b through conformational rearrangements. Once synthesis is initiated, LpoB affinity for PBP1b dramatically decreases and it dissociates from the synthesizing enzyme. Our results suggest that transient allosteric coupling between PBP1b and LpoB directs PG synthesis to areas of low peptidoglycan density, while simultaneously facilitating efficient lipoprotein redistribution to other sites in need of fortification.